Proposal for a Common Currency among Rich Democracies - Michael D. Bordo; Richard N. Cooper (Oesterreichische Nationalbank (OeNB), 2006)
Paper 1: This paper suggests that some time in the not-too-distant future the governments of the industrialized democracies – concretely, the United States, the European Union, and Japan – should consider establishing a common currency for their collective use. A common currency would credibly eliminate exchange rate uncertainty and exchange rate movements among major currencies, both of which are significant sources of disturbance to important economies. One currency would of course entail one monetary policy for the currency area, and a political mechanism to assure accountability. This proposal is not realistic today, but is set as a vision for the second or third decade into the 21st century. Europeans, in creating EMU, have taken a major step in the direction indicated. Their idea could be taken further. Paper 2: In this paper, we look at the major arguments for monetary simplification and unification before explaining why the nineteenth century utopia is an idea whose time has gone, not come.
Keywords: 330